Linear Variable Differential Transformer Design and Verification Using MATLAB and Finite Element Analysis - Al-Sharif, Lutfi; Kilani, Mohammad; Taifour, Sinan; Issa, Abdullah Jamal; Al-Qaisi, Eyas; Eleiwi, Fadi Awni; Kamal, Omar Nabil (IntechOpen, 2011)
None